Homo Sapiens vs. Homo Patiens or: How One Might Learn to Stop Worrying and Love AI - Blincoe, Adam (American catholic philosophical quarterly, 2025)
In this essay I present two philosophical anthropologies, one of agency (homo sapiens) and one of passivity (homo patiens). For biological and sociological reasons, the former has dominated human self-understanding. Recent technology, culminating in generative AI, threatens to make a passive anthropology plausible. If this happens, whole swaths of people may outsource the activities that make up life and instead seek a passive existence as subjects of experiences. I discuss current cultural dynamics that make this option attractive. To avoid this, we need properly attuned affective powers, including a healthy sense of disgust. This forms the basis of my anthropological argument for a liberal education. In the age of AI, the liberal arts can no longer be justified via economic marketability. Instead, they will need to be valued for their formation of students into persons who can use leisure well and who feel a proper disgust for homo patiens.